Handbook of incineration systems - Brunner, Calvin R. (McGraw-Hill, 1991)
This comprehensive handbook presents the information needed not only to design facilities for incinerating refuse, sludges, gases, radioactive, hazardous and other industrial wastes, but also the guidelines to upgrade existing facilities to conform to regulatory constraints.